Serogroup identification of meningococci by a modified antiserum agar method. - Craven, D E (1979)
Modifications in the antiserum agar method for serogroup identification of meningococci, which reduce the amount of group-specific antisera required and increase long-term storage of prepoured antiserum agar plates, are described.